Incidence of head and neck squamous cell carcinoma among subjects at high risk of lung cancer: Results from the Pittsburgh Lung Screening Study. Issue 9 (5th January 2015) - Dixit, Ronak; Weissfeld, Joel L.; Wilson, David O.; Balogh, Paula; Sufka, Pamela; Siegfried, Jill M.; Grandis, Jennifer R.; Diergaarde, Brenda
<x xml:space="preserve">Abstract</x> BACKGROUND Earlier detection and diagnosis of head and neck squamous cell carcinoma (HNSCC) should lead to improved outcomes. However, to the authors' knowledge, no effective screening strategy has been identified to date. In the current study, the authors evaluated whether it would be useful to screen subjects targeted for lung cancer screening for HNSCC as well. METHODS Medical records, death certificates, and cancer registry and questionnaire data were used to determine the number of observed incident HNSCC cases in the Pittsburgh Lung Screening Study (PLuSS), a cohort of current and former smokers aged ≥50 years with a ≥12.5 pack‐year smoking history. The expected number of cases was estimated using stratum‐specific incidence rates obtained from Surveillance, Epidemiology, and End Results data for 2000 through 2011. The standardized incidence ratio was calculated to examine the difference between the observed and expected number of cases. RESULTS Of the 3587 at‐risk participants in the PLuSS, 23 (0.64%) developed HNSCC over a total of 32, 201 person‐years of follow‐up. This finding was significantly higher than expected based on incidence rates obtained from the Surveillance, Epidemiology, and End Results program (13.70 cases expected; standardized incidence ratio, 1.68 [95% confidence interval, 1.06‐2.52]). The excess burden of HNSCC in the PLuSS was 28.9 cases per 100, 000 person‐years. Observed incident cases were significantly more often male, had started smoking at a younger age, smoked more per day, and had more pack‐years of smoking than the rest of the PLuSS at‐risk participants. CONCLUSIONS The results of the current study provide a rationale for offering head and neck cancer screening along with computed tomography screening for lung cancer. Randomized controlled trials that assess the effectiveness of adding examination of the head and neck area to lung cancer screening programs are warranted. Cancer 2015;121:1431–1435. © 2015 American Cancer Society.